The islands of Chaldea - Jones, Diana Wynne (Greenwillow Books, an imprint of HarperCollinsPublishers, 2014)
Aileen's family of magic makers includes Aunt Beck, the most powerful magician on Skarr, but her own magic does not show itself until a mission for the King and a magical cat help her find strength and confidence.